Job stressors and other risk factors related to the risk of hypertension among selected employees in Jakarta (Faculty of Medicine Universitas Indonesia, 2006)
Almost everyone, including employees, may develop hypertension. Several risk factors, including stresses in the work environment, are related to hypertension. The aim of this study is to identify these work-related risk factors in hypertension. A nested case-control study was conducted among office employees in Jakarta during May 2004. Employees with stage 1 or stage 2 hypertension (based on the United States of America Joint National Committee on high blood pressure 2003), or those taking antihypertensive drugs were designated as cases. As controls were employees with no history of hypertension. One case was randomly matched by gender with two controls. All risk factors for cases and controls were counted as of the reference date of diagnosis for cases. There were 70 cases and 140 controls aged 25 to 65 years. Hypertension was found to be related to the qualitative and quantitative increase in the workload, career development, age, obesity, current and past smoking habits, and a family history of hypertension. However, it was noted that role of ambiguity, role of conflict, and personal responsibility did not increase the risk of hypertension. Compared to those with low qualitative job stressor, those who had moderate or high qualitative job stressor had a seven-fold risk to be hypertensive [adjusted odds ratio (ORa) = 7.47; 95% confidence interval (CI) = 1.40-39.76]. In addition, relative to those who had low quantitative job stressor, those with moderate or high stressors were four times at risk to be hypertensive (ORa = 4.10; 95% CI = 1.06-15.90). In conclusion moderate or high qualitative and quantitative job stressors as well as career development increased risk hypertension. Therefore these stressors need to be prevented. (Med J Indones 2006; 15:177-84) Keywords: hypertension, qualitative job stressor, quantitative job stressor, career development